THE FAILURE ANALYSIS OF THE SINGLE-LAP MULTI-BOLT COMPOSITE JOINTS BASING ON THE CONTINUUM DAMAGE MODEL - ZHOU YinHua; HOU Chi; ZHAO MeiYing; WAN XiaoPeng (Jixie qiangdu)
In order to investigate the failure of composite multi-bolt joints,a continuum damage model for composites which achieved good agreements with experiments,and the Johnson-Cook plasticity model for bolts,were employed to model the singlelap multi-bolt composite joints in this paper. The effects on the composite bolted joints with variable clearances have been studied. It has been found that the clearance has slightly effects on the failure modes and loading responses of the joints,but exacerbates the secondary bending of single-lap joints,and the models proposed in the article have achieved relatively accurate load-displacement responses and ultimate failure loads of the whole joints in simulation.